2008
DOI: 10.1124/mol.107.043299
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Excitation-Coupled Calcium Entry in Myotubes Expressing Malignant Hyperthermia Mutation R163C Is Attenuated by Dantrolene

Abstract: Dantrolene is the drug of choice for the treatment of malignant hyperthermia (MH) and is also useful for treatment of spasticity or muscle spasms associated with several clinical conditions. The current study examines the mechanisms of dantrolene's action on skeletal muscle and shows that one of dantrolene's mechanisms of action is to block excitation-coupled calcium entry (ECCE) in both adult mouse flexor digitorum brevis fibers and primary myotubes. A second important new finding is that myotubes isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 59 publications
(76 reference statements)
5
92
1
1
Order By: Relevance
“…To determine whether the R174W mutation altered EC coupling, as has been demonstrated for other MH-causing mutations in either RyR1 (14)(15)(16)(17)(18)(19)(20)(25)(26)(27) or Ca V 1.1 (21), we measured myoplasmic Ca 2+ transients in the whole-cell configuration. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether the R174W mutation altered EC coupling, as has been demonstrated for other MH-causing mutations in either RyR1 (14)(15)(16)(17)(18)(19)(20)(25)(26)(27) or Ca V 1.1 (21), we measured myoplasmic Ca 2+ transients in the whole-cell configuration. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously characterized mutations in either channel have been found to promote activation of RyR1 during EC coupling and/or to enhance Ca 2+ entry via Ca V 1.1 (13)(14)(15)(16)(17)(18)(19)(20)(21). Thus, it has been proposed that augmented Ca 2+ movements via the EC coupling pathway or via the L-type current underlie the fulminant response to MH triggers.…”
Section: 4-dihydropyridine Receptor | α Ismentioning
confidence: 99%
“…In primary myotubes, depolarizing stimuli that do not substantially deplete SR Ca 2+ stores can rapidly activate extracellular Ca 2+ entry by a mechanism called excitation coupled Ca 2+ entry (ECCE) that occurs through a complex made up of RyR1 and DHPR, the latter having dual functions not only as the voltage sensor for EC coupling but also as an L-type Ca2+ channel [61,62]. Experimental evidence supporting a pathogenic role of enhanced ECCE in MHS was provided by Cherednichenko et al [63] in mice knocked in for the RYR1 p.R163C mutation. Studies on skeletal muscles from these mice demonstrated: (i) that they exhibited enhanced depolarization-induced Ca 2+ entry, (ii) that this influx of Ca 2+ did not occur via store activated Ca 2+ entry, but via ECCE and (iii) that it is sensitive to dantrolene, the drug that is clinically used to revert MH reactions.…”
Section: Disorders Associated With Cacna1s Mutationsmentioning
confidence: 98%
“…In this regard, RGK proteins may regulate a variety of cellular processes that have been linked to depolarization-dependent Ca 2+ entry such as maintenance of myoplasmic Ca 2+ levels during activity, 4 activation of transcription via NFAT translocation 20 and regulation of muscle strength 19 and mass (see below). Moreover, altered RGK protein-mediated modulation of depolarization-dependent Ca 2+ entry may potentially be involved in the pathophysiology of malignant hyperthermia, [21][22][23] central core disease, 20 and rippling muscle disease 24 since enhanced depolarization-dependent Ca 2+ entry is characteristic of these muscle disorders. The similar degree of inhibition between depolarizationdependent Ca 2+ entry and L-type current represents yet another commonality between these 2 modes of Ca 2+ flux into skeletal muscle (please see Table 4 of ref.…”
Section: Discussionmentioning
confidence: 99%